2014
DOI: 10.2147/jpr.s36446
|View full text |Cite
|
Sign up to set email alerts
|

Dosing considerations with transdermal formulations of fentanyl and buprenorphine for the treatment of cancer pain

Abstract: Opioids continue to be first-line pharmacotherapy for patients suffering from cancer pain. Unfortunately, subtherapeutic dosage prescribing of pain medications remains common, and many cancer patients continue to suffer and experience diminished quality of life. A large variety of therapeutic options are available for cancer pain patients. Analgesic pharmacotherapy is based on the patient’s self-report of pain intensity and should be tailored to meet the requirements of each individual. Most, if not all, cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…1,2001, to Mar. 31, 2013, we identified 267 958 prescriptions for transdermal fentanyl patches dispensed to 17 102 distinct pa-tients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2001, to Mar. 31, 2013, we identified 267 958 prescriptions for transdermal fentanyl patches dispensed to 17 102 distinct pa-tients.…”
Section: Resultsmentioning
confidence: 99%
“…1 Although available in a variety of forms, the most common form for outpatient use in Canada is the transdermal patch, which provides 3-day continuous delivery of the drug. Fentanyl was initially available in 25-, 50-, 75-and 100-μg/h patches.…”
mentioning
confidence: 99%
“… 11 , 18 , 19 , 23 While oral opioids are generally the first choice, 1 , 26 TD medications are recommended by guidelines for ongoing care of patients with cancer pain 1 and are preferred by many patients because they are noninvasive, easy to use, and their interference with daily activities is minimal. 18 , 24 , 27 TD buprenorphine and TD fentanyl are usually the treatment of choice for patients who are unable to swallow, patients with poor tolerance to morphine, and patients with poor compliance. 1 , 7 , 9 , 11 , 18 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…In prolonged opioid treatment, maintaining analgesia with minimal adverse effects requires minimal variation in opioid plasma levels. In this regard, slow transdermal opioid delivery from transdermal patches allows more effective analgesia and fewer adverse events than with oral or parenteral opioids, with lower rates of constipation, nausea, and sedation [ 17 ]. A meta-analysis of data derived from 8 prospective clinical studies, published between 1996 and 2004, and including 1,220 patients with cancer ( n = 657) or noncancer pain ( n = 563) showed that both fentanyl and morphine are effective by transdermal application [ 18 ], with improved pain scores after 28 days of treatment.…”
Section: Introductionmentioning
confidence: 99%